2017
DOI: 10.3934/jimo.2016018
|View full text |Cite
|
Sign up to set email alerts
|

Service product pricing strategies based on time-sensitive customer choice behavior

Abstract: Product pricing strategy has a significant impact on a service company's competitive edge. Considering the heterogeneous and time-sensitive customer choice behavior, monopoly service companies price their service products depending on cost parameters as well as time-sensitive customer choice behavior. According to the different time sensitivity, customers are classed into two groups (i.e., two market segments). By considering the impact of customer choice behavior, this paper investigates how a monopoly servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Shang and Liu [46] adopt a two-stage game to study the time-sensitive and quality-sensitive customer, and prove that quality differentiation plays a dual role in the time-based competition, either helping companies with larger time competitive advantage compete more effectively, or helping companies with smaller time competitive advantage seize the market and protect their market advantages. Zhang et al [47] study the strategy of monopolizing the service industry segment based on customer's time-sensitivity, compare the most profitable of the two strategies and find that the optimal profit of providing one service is always lower than the differentiation strategy. Li et al [48] study the impact of price sensitivity and delivery time on demand based on the supermodular game theory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shang and Liu [46] adopt a two-stage game to study the time-sensitive and quality-sensitive customer, and prove that quality differentiation plays a dual role in the time-based competition, either helping companies with larger time competitive advantage compete more effectively, or helping companies with smaller time competitive advantage seize the market and protect their market advantages. Zhang et al [47] study the strategy of monopolizing the service industry segment based on customer's time-sensitivity, compare the most profitable of the two strategies and find that the optimal profit of providing one service is always lower than the differentiation strategy. Li et al [48] study the impact of price sensitivity and delivery time on demand based on the supermodular game theory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The above research gives the methods and benefits of market segmentation. However, market segmentation in the supply chain will lead to consumer's self-selection behavior, which will affect the decision-making of supply chain members (Zhang et al, 2017;Zhang et al, 2015). Limited research focused on the negative effects of market segmentation.…”
Section: The Application Of Market Segmentationmentioning
confidence: 99%
“…But, consumers belonging to different segments have different preferences, and thus have different substitution behaviors (Lee and Eun, 2020), which is called consumer choice behavior (Khan and Mohsin, 2017). Consumer choice behavior under market segmentation strategy has been investigated from many perspectives (Wang and Wang, 2017;Zhang et al, 2017;Yang et al, 2019;Hwang ang Park, 2016;Aviv et al, 2019), such as supply chain decisions and coordination (Buell and Kalkanci, 2021;Kabul and Parlaktürk, 2019;Wang et al, 2020;Farshbaf-Geranmayeh and Zaccour, 2021). They found that, because of consumer choice behavior, dual-channel supply chain structure is not always better than single-channel supply chain structure (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To attract customers, some retailers such as Tesco, Casino and Patagonia have begun to attach the carbon footprint label with the products, which helps the customers to follow every step of the manufacturing process. Some retailers pay attention in promotional advertisements, in-store and out-store banners (Jian et al [18]) while some retailers focus on time-sensitivity of consumers (Zhang et al [53]). Thus, the CLSC needs to study the effect of the manufacturer's green innovation efforts and the retailer's marketing efforts.…”
mentioning
confidence: 99%